ANALISIS DAYA DUKUNG DAN PENURUNAN TIANG PANCANG MENGGUNAKAN DATA PDA TEST DAN PROGRAM PLAXIS PADA PEMBANGUNAN GEDUNG LABORATORIUM DAN KULIAH TERPADU UNIVERSITAS BORNEO TARAKAN - Hasrullah Hasrullah; Syarif Iswandi; Dandung Novianto (Universitas Islam Balitar Blitar, 2021)
The foundation is the structure of the lower part of a building that is directly related to the ground or part of the building that is located below the ground surface which has the function of bearing the load of other parts of the building above it. There are various kinds of dynamic bearing capacity of the pile foundation, one of which is used with dynamic field test results, namely the PDA Test. The purpose of this research is to determine the carrying capacity of piles using PDA Test data then the results of the analysis will be compared with the results of calculations with Plaxis 2D V.8. The results of the calculation of the bearing capacity of the pile using PDA Test data obtained the largest value, namely 103 tons and the results of the carrying capacity using the Bagemann method obtained the value of 149.51 tons. The calculation of the pile settlement in the CAPWAP data is 12.97 mm at the P 113 pile and the calculation result of the maximum settlement of the pile in the Plaxis calculation is 3.50 mm the estimated single pile settlement meets the safe/permitted requirements.